2014
DOI: 10.1111/tpj.12508
|View full text |Cite
|
Sign up to set email alerts
|

A homolog of ETHYLENE OVERPRODUCER, OsETOL1, differentially modulates drought and submergence tolerance in rice

Abstract: SUMMARYSubmergence and drought are major limiting factors for crop production. However, very limited studies have been reported on the distinct or overlapping mechanisms of plants in response to the two water extremes. Here we report an ETHYLENE OVERPRODUCER 1-like gene (OsETOL1) that modulates differentially drought and submergence tolerance in rice (Oryza sativa L.). Two allelic mutants of OsETOL1 showed increased resistance to drought stress at the panicle development stage. Interestingly, the mutants exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 53 publications
0
56
0
Order By: Relevance
“…It also reported that ethylene could regulate drought tolerance in maize and rice (Habben et al, 2014;Du et al, 2014). However, its role in salt response of rice is still unclear.…”
Section: Perspectivesmentioning
confidence: 95%
“…It also reported that ethylene could regulate drought tolerance in maize and rice (Habben et al, 2014;Du et al, 2014). However, its role in salt response of rice is still unclear.…”
Section: Perspectivesmentioning
confidence: 95%
“…Similarly, better drought and salinity tolerance was observed in Arabidopsis (Cheng et al 2013 ) and tomato (Pan et al 2012 ) plants overexpressing ERF -1 and ERF-5, respectively. Further, ET overproducer 1-like ( ETOL1 )-overexpressing rice plants was found more tolerant to drought and submergence (Du et al 2014 ). It can be concluded that ET metabolism and signaling pathways infl uence various stress responses in plants (Krannich et al 2015 ).…”
Section: Genetic Engineering Of Ethylene Metabolismmentioning
confidence: 98%
“…Previous studies indicate that ETHYLENE OVERPRODUCER 1-like gene [20] and Sadenosylmethionine synthetase [19] were in response to flooding and drought stresses. The research using common protein between flooding and drought provided new insights to improve plant tolerance.…”
Section: Fermentation and Protein Synthesis/degradation Are Increasedmentioning
confidence: 99%
“…In rice, the ethylene production and energy metabolism were modulated to adapt to flooding and drought stresses [20]. In wheat, proteins related to glycolysis and cell wall structure were decreased; while defense related proteins were increased under flooding [21]; and the metabolism related to gliadins synthesis was enhanced under drought [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation